2013
DOI: 10.1590/s0104-66322013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized Lactobacillus acidophilus produced from whey and alginate

Abstract: -An analysis was made of the use of whey fermentation by Lactobacillus acidophilus LA-5 for encapsulated probiotic bacteria cell production. Fermentation was done in a 2-liter Biostat B Fermentor at 28±1 ºC without air supply and agitation maintained at 200 rpm. Different processing conditions were studied using Center Composite Design applied to Surface Response Methodology. Maximum cell yield (2.7 x10 10 NMP/mL for 36 hours) was achieved with 30.85 g/L of lactose, a pH value of 6.45 and 1.04 g/L of inoculum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Jyoti et al (2003), moreover, demonstrated a diauxic growth on multiple substrates (i.e., glucose+ citrate; glucose + lactate) also in the genetically related species L. rhamnosus . On the contrary, Rosa et al (2013) found that L. acidophilus grown on a whey-based medium did not exhibit a diauxic pattern, suggesting that the lactose was hydrolyzed into glucose and galactose and both sugars were utilized simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…Jyoti et al (2003), moreover, demonstrated a diauxic growth on multiple substrates (i.e., glucose+ citrate; glucose + lactate) also in the genetically related species L. rhamnosus . On the contrary, Rosa et al (2013) found that L. acidophilus grown on a whey-based medium did not exhibit a diauxic pattern, suggesting that the lactose was hydrolyzed into glucose and galactose and both sugars were utilized simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…Nesta situação os parâmetros associados ao conhecimento influem no treino da rede e o MHRN passa a gerar estimativas melhores dos e extrapolações de resultados mesmo com o uso de um menor número de pontos que as Na Figura 1 é representada uma RNA tradicional ( Fig.1a) e uma configuração de MHRN respostas do modelo construído com os princípios que descrevem o conhecimento do processo (por exemplo integração das equações de um modelo diferencial) gera respostas (d) que influem nos pesos que possibilitam a rede a ajustar os os neurônios. Uma exemplo que que as respostas obtidas não situação que estas são negativas quando fisicamente MHRN (Psichogios, Ungar, 1992-adaptado) produção de células de Lactobacillus em soro de leite utilizando o MHRN, avaliar a estabilidade das células geradas neste estudo para diferentes tempos de fermentação e avaliar as previsões associadas ao MHRN que podem Foi utilizado Lactobacillus acidophilus La5 cultivado por fermentação batelada em soro de queijo reconstituído nas condições otimizadas presentes na literatura (Rosa et al;2013) correspondentes a concentração de lactose de 31,0 g/L, pH de 6,45 e 1,04 g/L de inóculo.…”
Section: Methodsunclassified
“…As células obtidas por fermentação de 40, 60 e 80h foram centrifugadas e secas em estufa de circulação forçada a 45 o C por 2h e submetidas à teste de viabilidade que foi definido como a avaliação da perda de viabilidade após o armazenamento por 5 dias. Nesta avalição a quantificação das células foi feita por plaqueamento em ágar MRS (Rosa et al 2013). A viabilidade celular foi definida como percentagem de células vivas restantes.…”
Section: Avaliação Das Células Na Produção De Insumos Para Ração Animalunclassified
“…Research has shown that LAB encapsulation increases viability in dairy products without changing product color, acidity or taste ( Rosa et al, 2013 ). This methodology was also applied to optimize the transfer of vaccine plasmids into intestinal cells, as described by Coelho-Rocha et al (2018) .…”
Section: Targeting Of Lactococcus Lactis To Specifmentioning
confidence: 99%